Social innovation in urban and regional development. Perspectives on an emerging field in planning and urban studies. - (:unkn) unknown (Selbstverl., 2018)
Der Sammelband "Soziale Innovation in der Stadt- und Regionalentwicklung" rückt die laufenden Forschungen von Nachwuchswissenschaftlern in den Fokus. Der neu aufkommende Diskurs über soziale Innovation (SI) wird durch eine Vielzahl von Themen, Fallstudien und methodischen Ansätzen abgedeckt, die im Rahmen der Internationalen Sommerschule 2017 der Deutschen Akademie für Raumforschung und Raumplanung (ARL) in Kooperation mit der Universität Wien und der Österreichischen Akademie der Wissenschaften diskutiert wurden. Als ein Ergebnis wurde ein breiteres Verständnis von SI in der Stadt- und Regionalentwicklung entwickelt, indem jüngste Initiativen und Strategien von SI in diesem Bereich diskutiert wurden.

This edited volume on social innovation in urban and regional development brings the ongoing research of early-career researchers into focus. The re-emerging discourse on social innovation (SI) is covered through a variety of topics, case studies and methodological approaches that were discussed during the International Summer School 2017 of the German Academy of Spatial Research and Planning (ARL) in cooperation with the University of Vienna and the Austrian Academy of Sciences. As a result, a broader understanding of SI in urban and regional development has been developed by discussing recent initiatives and strategies of SI within this field.
Keywords: Stadtentwicklung; Regionalentwicklung; Planungstheorie; Raumwissenschaft; Partizipation; Stadtteilplanung; Nachbarschaft; Innovationsforschung; Sozialinnovation